Competitiveness Analysis of Indonesian Ginger Exports 2012-2021 - Akbar Arsy; Afdri Jiyaris Gamaradika; Gea Dwi Asmara (Jurnal Mebis, 2024)
Indonesia is an agrarian country which has a land and climate that supports growing spices such as ginger, Indonesia is able to compete in ginger exports in international trade, one of the influences of economic development, Indonesia exports in Japan, USA, Malaysia consecutively in 2012-2021 this analysis uses the RCA method to measure comparative advantage in international trade, this data is also taken from UN Comtrade and International Trade Centre (ITC) sources. The results showed that Indonesia has a comparative advantage which has a value of more than 1 in the RCA calculation in international trade with Japan, USA, Malaysia, therefore it requires a good strategy to be supported by the government in exporting ginger and increasing the productivity of ginger farmers.